Programming in Objective-C, Fourth Edition - Kochan, Stephen (Addison-Wesley Professional, 2011)
Programming in Objective-C, Fourth Edition Updated for iOS 5 and ARC Programming in Objective-C is a concise, carefully written tutorial on the basics of Objective-C and object-oriented programming for Apple's iOS and Mac platforms. The book makes no assumptions about prior experience with object-oriented programming languages or with the C language (which Objective-C is based upon). Because of this, both beginners and experienced programmers alike can use this book to quickly and effectively learn the fundamentals of Objective-C. Readers can also learn the concepts of object-oriented programming without having to first learn all of the intricacies of the underlying C programming language. This unique approach to learning, combined with many small program examples and exercises at the end of each chapter, makes Programming in Objective-C ideally suited for either classroom use or self-study. The fourth edition of this book has been updated to cover the significant changes that first appeared in iOS 5 and Xcode 4.2, including the use of Automatic Reference Counting (ARC) to improve and simplify memory management in Objective-C programs.